Economic consequences of over‐diagnosis of threatened preterm labor. Issue 2 (14th February 2018) - Coloma, Marta; Kang, Fatima; Vallejo‐Torres, Laura; Díaz, Paloma; Méndez, Yurena; Álvarez de la Rosa, Margarita
Abstract: Objective: To investigate whether adherence to a cervical length‐based protocol can reduce both unnecessary admissions and the socioeconomic costs associated with inappropriately admitted patients. Methods: The present retrospective observational study included women admitted for threatened preterm labor (TPL) at 24–34 weeks of pregnancy to a tertiary hospital in the Canary Islands, 2009–2014. Data were reviewed from all patients admitted for TPL. Those with a long cervix (>25 mm) were classified as "inappropriate admissions", and both the economic burden based on diagnosis‐related group (DRG) and the social costs associated with sick leave for these women were calculated. Results: During the 6‐year study period, 430 women were admitted for TPL. The rate of inappropriate hospital admissions was 45% in the first year, but was reduced to 23% in the final year ( P <0.001); the premature delivery rates in these years did not differ ( P =0.224). The mean DRG‐based cost of the admission per patient with a long cervix was EU euros €2099. The total annual costs from inappropriate admission (both social security sick leave costs and hospital costs) were estimated to be up to €571 047.37 during the 6‐year study period, and reduced from €60 420.76 in 2009 to €29 998.04 in 2014. Conclusion: Reductions in inappropriate admissions from applying cervical length‐based management protocol could reduce healthcare costs without increasing the incidence of premature delivery. Abstract : Adherence to clinical protocol helped to reduce total healthcare and social costs related to threatened preterm labor treatment without increasing the premature delivery rate. This article includes a Spanish translation of the Abstract, available in the Supporting Information section.